Development and Application of Credit Scoring Models in Retail Decision-Making Processes of Financial Institutions - Borodin, Dmitry (2016)
Usage of outputs from credit scoring models within decision-making process is often neglected in the existing literature. Nonetheless, it is a critical component of a successful lending process. This thesis introduces the concept of credit scoring and discusses steps typically employed within model development process. This thesis then provides an overview of how modeling outputs are typically used in lending. The thesis primarily focuses on definition of cut-offs points, policy and business rules, limit assignment and risk based pricing. The introduced approaches are modeled in the last part of the thesis.